2020
DOI: 10.1126/sciadv.aba4905
|View full text |Cite
|
Sign up to set email alerts
|

Germline genomic patterns are associated with cancer risk, oncogenic pathways, and clinical outcomes

Abstract: There is an ongoing debate on the importance of genetic factors in cancer development, where gene-centered cancer predisposition seems to show that only 5 to 10% of the cancer cases are inheritable. By conducting a systematic analysis of germline genomes of 9712 cancer patients representing 22 common cancer types along with 16,670 noncancer individuals, we identified seven cancer-associated germline genomic patterns (CGGPs), which summarized trinucleotide mutational spectra of germline genomes. A few CGGPs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…only SNVs were used in the SBS signatures we mainly focused on; (2) the read depths covering the mutated sites should be larger than 10; (3) the variant allele frequency (VAF) should be larger than 1%, consistent with our previous research 16 . As a result, 10,088 samples were retained for subsequent analysis.…”
Section: Somatic Mutation Data Collectionsupporting
confidence: 70%
See 2 more Smart Citations
“…only SNVs were used in the SBS signatures we mainly focused on; (2) the read depths covering the mutated sites should be larger than 10; (3) the variant allele frequency (VAF) should be larger than 1%, consistent with our previous research 16 . As a result, 10,088 samples were retained for subsequent analysis.…”
Section: Somatic Mutation Data Collectionsupporting
confidence: 70%
“…We used the ‘maf2vcf perl script (https://github.com/mskcc/vcf2maf) to convert the MAF to VCF files. In addition to the filtration implemented by TCGA, the mutations were further filtered using these criteria: (1) only SNVs were used in the SBS signatures we mainly focused on; (2) the read depths covering the mutated sites should be larger than 10; (3) the variant allele frequency (VAF) should be larger than 1%, consistent with our previous research 16 . As a result, 10,088 samples were retained for subsequent analysis.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…Germline genome may substantially affect immune capacity in cancer patients at a population level, including the response rate to cancer immunotherapy (42). Xue et al comprehensively analyzed the germline genomes of nearly 20,000 patients in 22 common cancer types and concluded that germline genomic patterns could inform treatment and clinical outcomes (43). Based on the prognosis-related immune terms, we identified IRS model to predict PCa patient survival and immunotherapy response rate.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models and epidemiological studies suggest that the risk of developing metastasis after breast cancer diagnosis depends on the characteristics of the tumour and germline gene variants [8,9]. Furthermore, Xu et al, have shown how germline variants of natural killer cells in the tumour immune microenvironment can sway metastasis risk in several cancers [10]; they have also identified germline genomic patterns that contribute to cancer progression and metastasis [11].…”
Section: Introductionmentioning
confidence: 99%